2022
DOI: 10.1177/01423312221081505
|View full text |Cite
|
Sign up to set email alerts
|

Vibration control of a translational coupled double flexible beam system using sliding mode neural network fuzzy control

Abstract: A sliding mode neural network fuzzy control (SMNNFC) method is investigated to suppress the vibration of a translational coupled double flexible beam system, equipped with an AC servomotor and several piezoelectric actuators. Adjacent beams and slider moving frame are connected at the tip by elastic springs. Based on the finite element method, the system model is established to recognize the vibration characteristics. Furthermore, two laser displacement sensors are used to decouple the first two bending modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In the visual measurement control of the alignment system, the camera needs to rotate to find the target due to the limitation of the angle of view. Therefore, the visual measurement module is also controlled by the fuzzy controller, and the control rule is the same as the controller of the discharge arm (Gongye et al, 2022; Jalali and Moghaddam, 2022; Qiu and Chen, 2022; Song et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In the visual measurement control of the alignment system, the camera needs to rotate to find the target due to the limitation of the angle of view. Therefore, the visual measurement module is also controlled by the fuzzy controller, and the control rule is the same as the controller of the discharge arm (Gongye et al, 2022; Jalali and Moghaddam, 2022; Qiu and Chen, 2022; Song et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The literature [18] proposes an adaptive fuzzy control strategy for single-link flexible joint robot (SFRM) with specific functions, in which fuzzy logic system is used to identify unknown nonlinear terms. The literature [19] studies a sliding mode neural network fuzzy control method to suppress the vibration of a double flexible beam system. In order to adjust the displacement and clamping force of flexible grippers, a hybrid force/position control strategy based on PID controller and fuzzy sliding mode controller was proposed in the literature [20].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results show that the controller significantly improves the vibration-suppression and ride quality of the vehicle [8]. Qiu Zhiqiang proposed a sliding-mode neural-network fuzzy control method to suppress the vibration of the coupled double-flexible-beam system, and experiments showed that the control method has advantages in suppressing the large amplitude and low amplitude of the coupled double-flexible-beam system [9]. To further improve the target-tracking efficiency of the snake robot, Liu Zhifan proposed an improved double-power-reaching law and verified the effectiveness and practicability of the proposed strategy through comparative analysis and simulation [10].…”
Section: Introductionmentioning
confidence: 99%